2003
DOI: 10.1097/01.asn.0000065632.32856.4c
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A Amplifies Ca2+ Signaling Pathway in LLC-PK1 Cells through the Inhibition of Plasma Membrane Ca2+ Pump

Abstract: ABSTRACT. Cyclosporine A (CsA), a neutral, highly hydrophobic cyclic peptide with 11 amino acids, is currently the most widely used immunosuppressive drug for preventing graft rejection and autoimmune diseases. Despite its efficacy, the use of CsA is limited by severe side effects, mainly nephrotoxicity and arterial hypertension. Single cell microfluorimetry was used to evaluate the role of CsA on Ca2+ signaling pathway in intact cells of the porcine proximal tubule-like cell line LLC-PK1; the assay of the in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
10
1
Order By: Relevance
“…This finding is different from previous results, but these discrepancies might be attributed to a different effect of CsA on distinct PMCA isoforms (PMCA1 and PMCA4), with PMCA4 being the isoform predominantly expressed in platelets, more likely insensitive to CsA. 17,33,34 To identify the SERCA isoform regulated by CsA, we stimulated platelets with Thr in the presence of specific inhibitors of the different SERCA isoforms in these cells (SERCA2b and SERCA3). 18 -21 When SERCA3 was inhibited by TBHQ, CsA was still able to alter Thr-induced Ca 2ϩ mobilization, including the ability of platelets to accumulate Ca 2ϩ into intracellular stores; however, when SERCA2b was inhibited by TG, CsA was unable to modify the Thr-evoked response, thus indicating that SERCA2b activity was inhibited in the presence of CsA.…”
contrasting
confidence: 87%
“…This finding is different from previous results, but these discrepancies might be attributed to a different effect of CsA on distinct PMCA isoforms (PMCA1 and PMCA4), with PMCA4 being the isoform predominantly expressed in platelets, more likely insensitive to CsA. 17,33,34 To identify the SERCA isoform regulated by CsA, we stimulated platelets with Thr in the presence of specific inhibitors of the different SERCA isoforms in these cells (SERCA2b and SERCA3). 18 -21 When SERCA3 was inhibited by TBHQ, CsA was still able to alter Thr-induced Ca 2ϩ mobilization, including the ability of platelets to accumulate Ca 2ϩ into intracellular stores; however, when SERCA2b was inhibited by TG, CsA was unable to modify the Thr-evoked response, thus indicating that SERCA2b activity was inhibited in the presence of CsA.…”
contrasting
confidence: 87%
“…In microsomal membrane vesicles, the ATPase activity was reduced to about 12% by orthovanadate (37). Cyclosporin A is frequently used as P-gp inhibitor but inhibits also other ATPases such as Na + / K + -ATPases (43) and Ca 2+ -pumps (44,45). One hundred M cyclosporin A reduced the basal ATPase activity of P388/ ADR and P388 rafts to about 60% and 70%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the contrast between the efficacy of CSA as an immunosuppressant and its high nephrotoxicity, many studies have been conducted to understand the mechanisms of CSA-induced nephrotoxicity. It has been shown that renal arteriolar constriction [4], direct fibrogenic effect on human tubulointerstitial cells [5], amplification of Ca 2+ signaling pathway [36], inhibition of COX-2 expression in response to low salt intake [37], inhibition of the adaptive responses to hypertonicity occurring during the urinary concentrating mechanism [38]and apoptosis involving mitochondrial injury [39]may contribute to CSA-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%